TOPICALITY OF ELECTRONIC MARKETING IN WORLD AND IN LATVIA - Nikolajeva, Anna; Muravjovs, Dmitrijs; Adejanovs, Dairis; Zorins, Aleksejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Paper theme: Topicality of electronic marketing in World and in Latvia. The aim of this paper was to explore electronic marketings topicality’s in World and Latvia. Nowdays in World e-commerce and e-marketing is commonplace for people. As a result of paper, authors did a conclusion, that enterprises in Latvia didn’t unaware the posibilities of e-marketing, but e-marketing topicality in World is very high. Most important thing in e- marketing ir strategy, because every enterprice need to choose priorities. If it’s a web page, then need to define needs. It’s not possible to use all e-marketing tools together, but it’s possible to establish a complex. In this way enterprice have a chance to attract new clients and business partners. The best example is Burberry Group Plc. Brend understood that they need to integrate in Internet. Burberry Group Plc divert 60% of his marketing budget to realize it’s e-marketing strategy. In the result increase profit, and increase interest form customers and business partners. E-marketing is topical and it always will be, while technologies is progresing stays question about them presentation format to custumer.